Association of progressive outer retinal necrosis and varicella zoster encephalitis in a patient with AIDS. Issue 11 (November 1996) - van den Horn, G J; Meenken, C; Troost, D
Abstract : BACKGROUND: A patient with AIDS who developed the clinical picture of bilateral progressive outer retinal necrosis (PORN) in combination with varicella zoster encephalitis is described. The picture developed more than 2 years after an episode of ophthalmic zoster infection, and following intermittent exposure to oral acyclovir because of recurrent episodes of cutaneous herpes simplex infection. METHODS: Aqueous humour, obtained by paracentesis of the anterior chamber, was analysed using immunofluorescence and polymerase chain reaction (PCR). Postmortem analysis of eye and brain tissue was performed by using conventional techniques and in situ hybridisation. RESULTS: While conventional techniques all failed to detect a causative agent, analysis of the aqueous humour using PCR, and histological examination of necropsy specimens from eyes and brain using in situ hybridisation were conclusive for the diagnosis varicella zoster virus (VZV) infection. CONCLUSION: This case documents the presumed association of PORN and VZV encephalitis in a severely immunocompromised AIDS patient.